Особливості будови елементарного пагона та пагонової системи деяких видів роду Coelogyne Lindl. (Orchidaceae Juss.) - Gyrenko, O.G. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2018)
Objective – to investigate morphological peculiarities of elementary shoot of three species of the genera Coelogyne Lindl. (C. ovalis Lindl., C. speciosa (Blume) Lindl., C. cristata Lindl.). Material and methods. The raw material derived from living plant collection of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. The study of vegetative and reproductive organs was performed by dissection and study of buds and shoots using “STEMI 2000C”. To characterize vegetative and generative organs used atlas on descriptive morphology of higher plants. Results. Rhizome part of shoot consist from 6 (C. speciosa) to 13 (C. ovalis) meromes, on which are formed from 2 (C. cristata) to 4 (C. ovalis) axillary buds; orthotropic vegetative part consist of 2–4 meromes. Generative part of C. ovalis develops only after complete formation of the pseudobulb and leaves and from the upper bud develops a shoots of the next branching order. From the upper bud of C. speciosa develops a shoot with synanthous type of inflorescence. From the upper bud of C. cristata develops a shoot, which completely forms only a generative part, and from below bud develops a shoot of renovation. Conclusions. The obtained results indicate that plants of the genus Coelogyne have the vegetativelygenerative elementary shoot. C. ovalis plants have hysteranthous inflorescence and dimonochazial branching type, C. speciosa plants – synanthous developmental inflorescence type and dimonochazial branching type, C. cristata plants – heteranthous type of inflorescence and monodichasial branching type of shoot. Plants of all species under study observed the simultaneous development of two shoots.